Poland's agriculture: serious competitor or Europe's poorhouse? Survey results on farm performance in selected Polish voivodships and a comparison with German farms - Martin Petrick (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2001)
The aim of this paper is to present an analysis of farm-level data collected in a survey of 464 Polish farms in 2000. Performance indicators of farms in three Polish voivodships are compared with farm accountancy data from two German Länder. The results show that Polish farms were much less profitable than their German counterparts. The gap in income levels is much higher between persons employed in the agricultural sector than between average working persons in the two countries. Living standards within the Polish farm sector decline from the north-west to the south-east. The analysis suggests that the lower profitability of farms is a consequence of pronounced structural deficiencies due to a quite unfavourable workforce-land ratio on Polish farms and hardly a result of lower product prices. Serious technical and economic inefficiencies in the production process become visible in the data. There is a generally conservative attitude among farmers that prefers the continuation of farming over leaving the sector. Nevertheless, income from agriculture is to a substantial extent complemented by off-farm employment in the southern regions. Formal education of farm managers and access to finance appeared not to be crucial for their economic success in the past, although especially the most profitable farms in the north did not obtain as much credit as desired. Our overall conclusion is that Polish farms currently are in the midst of a regional, economic, and social differentiation process fuelled by huge imbalances in terms of income levels between rural and urban population groups. This process is however seriously slowed down or even halted by a number of effective institutional barriers, particularly with regard to rural labour markets. These barriers should be properly addressed by a formulation of future policies in order to avoid further social frictions in the course of the Polish EU accession. – – Der Beitrag stellt die Ergebnisse einer Analyse von einzelbetrieblichen Kennzahlen vor, die im Rahmen einer Befragung von 464 polnischen Landwirten im Jahre 2000 erhoben wurden. Die Analyse stützt sich auf den Vergleich von landwirtschaftlichen Betrieben in drei polnischen Woiwodschaften und zwei deutschen Bundesländern. Die Ergebnisse zeigen, dass die polnischen Betriebe deutlich geringere Gewinne erzielen als ihre deutschen Vergleichspartner. Der Unterschied im Einkommensniveau zwischen Beschäftigten in der Landwirtschaft ist wesentlich höher als der zwischen durchschnittlichen Arbeitnehmern in beiden Ländern. Das Einkommensniveau innerhalb des polnischen Agrarsektors sinkt vom Nordwesten zum Südosten des Landes. Die Analyse legt nahe, dass die geringere Rentabilität der Betriebe in Polen in erster Linie auf Strukturdefizite als Konsequenz eines ungünstigen Verhältnisses zwischen Arbeitskraftbesatz und Nutzfläche zurückgeht und kein Resultat unterschiedlicher Produktpreisniveaus ist. Die Daten weisen weiterhin auf deutliche technische und wirtschaftliche Ineffizienzen im Produktionsprozess hin. Polnische Landwirte zeigen eine allgemein konservative Haltung, sie ziehen eine Fortsetzung der Tätigkeit als Landwirt einer außerlandwirtschaftlichen Beschäftigung vor. Dennoch werden vor allem in den südlichen Regionen landwirtschaftliche Einkommen weithin durch nichtlandwirtschaftliche Einkommensquellen ergänzt. Die formale Ausbildung der Landwirte sowie Zugang zu Krediten erwiesen sich in der Vergangenheit als überwiegend nicht entscheidend für den wirtschaftlichen Erfolg, obwohl besonders die rentabelsten Betriebe im Norden des Landes nicht in der Lage waren, Kredite im gewünschten Umfang zu erhalten. Wir ziehen als allgemeine Schlussfolgerung, dass sich die polnischen Betriebe inmitten eines regionalen, wirtschaftlichen und sozialen Ausdifferenzierungsprozesses befinden, der in erster Linie durch die großen Unterschiede im Einkommensniveau zwischen ländlichen und städtischen Bevölkerungsgruppen verursacht wird. Allerdings wird dieser Prozess durch effektive institutionelle Hindernisse, besonders im Hinblick auf den ländlichen Arbeitsmarkt, stark verlangsamt oder sogar zum Stehen gebracht. Diesen Hindernissen sollte durch künftige Politikmaßnahmen angemessen begegnet werden, um weitere soziale Verwerfungen im Laufe des polnischen EU Beitritts zu vermeiden.
urn:nbn:de:gbv:3:2-23022
Keywords: Q12; C81; P32; 330; agriculture; farm performance; survey data; Poland; Germany; Landwirtschaft; einzelbetriebliche Kennzahlen; Befragungsdaten; Polen; Deutschland; Landwirtschaft; Betriebsvergleich; Rentabilität; Wirtschaftlichkeit; Internationaler Wettbewerb; Polen; Deutschland